2022
DOI: 10.1101/2022.07.22.501075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative mapping of the dog epigenome: reference annotation for comparative inter-tissue and cross-species studies

Abstract: The domestic dog has become a valuable model in exploring multifaceted diseases and biology important for human health. Large-scale dog genome projects produced high-quality draft references but still lack comprehensive annotation of encoded functional elements. Through the integrative next generation sequencing of transcriptomes paired with histone marks and DNA methylome profiling of 11 adult tissue types, implemented in a cross-species approach, we generated a reference epigenome of a domesticated dog. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Our recent studies involving genomic and epigenomic comparisons across tissues of different species also revealed that chromatin map overlaps more between canines and humans (~40-50%) than between mice and humans (~10-20%). Furthermore, we also found that super enhancers were more highly conserved between canines and humans (~90% at ~50% minimum mismatch ratio) than between humans and mice (~30% at ~50% minimum mismatch ratio) 21 . Thus, the epigenetic changes affected by the environment might be more similar between canines and humans than between mice and humans.…”
Section: Comparative Oncology: New Insights Into a Human Cancermentioning
confidence: 60%
“…Our recent studies involving genomic and epigenomic comparisons across tissues of different species also revealed that chromatin map overlaps more between canines and humans (~40-50%) than between mice and humans (~10-20%). Furthermore, we also found that super enhancers were more highly conserved between canines and humans (~90% at ~50% minimum mismatch ratio) than between humans and mice (~30% at ~50% minimum mismatch ratio) 21 . Thus, the epigenetic changes affected by the environment might be more similar between canines and humans than between mice and humans.…”
Section: Comparative Oncology: New Insights Into a Human Cancermentioning
confidence: 60%
“…To assess global properties of the ATAC and methylation datasets, we performed feature level analysis on individual ATAC‐seq peaks and RRBS‐seq DNAm sites (15,417 ATAC peaks and 13,336 CpG sites after quality control filtering, see Section 4: Methods). First, we mapped each locus to the Epigenome Catalog of the Dog, a multi‐tissue canine chromatin state map (EpiC Dog; Son et al., 2023) to approximate a functional annotation for each feature. EpiC Dog is a curated repository of regulatory elements across chromatin datasets collected from 11 different tissue types in the companion dog (Figure S2a; Son et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…First, we mapped each locus to the Epigenome Catalog of the Dog, a multi‐tissue canine chromatin state map (EpiC Dog; Son et al., 2023) to approximate a functional annotation for each feature. EpiC Dog is a curated repository of regulatory elements across chromatin datasets collected from 11 different tissue types in the companion dog (Figure S2a; Son et al., 2023). PBMCs were not profiled in EpiC Dog, so we chose to compare to the annotations from canine spleen tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Thus we used canine mammary gland tumor cell lines; CHMp for primary tumor and CHMm for metastases (derived from metastatic lung pleural effusion) originated from same individual [24]. Canine breast cancer cell lines CHMp and CHMm are used due to its natural occurrence and the gene regulatory sequence of dogs is more similar to humans than mice [19,25].…”
Section: Resultsmentioning
confidence: 99%
“…Glycolysis is a key metabolic pathway involved in energy production and biosynthesis in cancer cells [24]. Additionally, glycolysis is closely associated with tumor metastasis [25]. Exosomemediated metabolic reprogramming has been shown to play a crucial role in tumor microenvironment formation and tumor progression [26].…”
Section: Discussionmentioning
confidence: 99%